A study on factors affects competency level of trainers at Sharp Manufacturing Corporation (M) Sdn Bhd, Batu Pahat Johor / Syahida Adila Mohamad Yes - Mohamad Yes, Syahida Adila (2010)
Competency can be described as an integrated set of human resource activities aimed at optimizing the development and the use of employee competencies in order to increase individual effectiveness, and, subsequently, to increase organizational effectiveness. Due to growing importance, the present study was implemented in order to explore the factors that will affect the competency level of trainers. There are three factors have been used to determined the competency level of trainer which are includes, intrinsic motivation, training and compensation. Multiple regressions method, reliability analysis, Pearson’s correlation coefficient, Frequency analysis, correlation and ANOVA Test were conducted in order to complete the objectives in this study. Based on the results, it was founds that there are strong relationship existed between these three variables in influencing the competency level of trainers.